Dynamic migration method of key virtual network function based on risk awareness - Shaohu DING; Jichao XIE; Peng ZHANG; Liming PU; Yunjie GU (Tongxin xuebao)
Aiming at the problems that traditional dynamic migration methods have many migration nodes,high migration frequency,and long service function chain (SFC) link path after migration when dealing with side channel attack,a dynamic migration method of critical virtual network function (VNF) based on risk awareness was proposed.In order to reduce the number of migrated nodes,only the key VNF with private information was migrated.Combined with the side channel attack detection system,the triggering migration was performed on the critical VNF which were under attack,and the key VNF was also periodically migrated according to the side channel information leakage model.Finally,a multi-attribute node sorting method base on the technique for order preference by similarity to ideal solution was used to select the migration destination server to avoid the path being too long after migration.Experiments show that the proposed method has a lower number of migration nodes and migration frequency when achieving the same side channel attack defense performance,and effectively avoids the problem that the SFC path is too long after migration.